IMPLEMENTASI SISTEM INFORMASI PENJUALAN SUKU CADANG TRUCK STUDI KASUS CV. INDO BANGUN PERKASA MOTOR - Tri Yuni Rachmawati; Amin Sadiqin (Jurnal Bina Bangsa Ekonomika, 2023)
INDO BANGUN PERKASA MOTOR Surabaya or often referred to as IBPM is a sole owner engaged in the sale of truck spare parts. The purpose of this survey is to collect information about CV sales accounting data system. INDO BANGUN PERKASA MOTOR Surabaya. This is a type of descriptive and qualitative research, in which the writer explains and analyzes the results of field observations and interviews. The authors draw the following conclusions based on their findings: theoretically, the accounting information system for the sale of used spare parts provides fairly reliable information, such as the suitability of the obligations and responsibilities of each part, the optimization of each part. related functions and functions, and the availability of the necessary documentation. the suitability of the accounting records used, and the suitability of the system used to compile them.